Bayesian Inference for Training of Long Short Term Memory Models in Chaotic Time Series Forecasting - Rodríguez Rivero, Cristian (2019)
Fil: Rodríguez Rivero, Cristian. Universidad Nacional de Córdoba; Argentina.